2016
DOI: 10.1037/xan0000102
|View full text |Cite
|
Sign up to set email alerts
|

Learning to inhibit the response during instrumental (operant) extinction.

Abstract: Five experiments tested implications of the idea that instrumental (operant) extinction involves learning to inhibit the learned response. All experiments used a discriminated operant procedure in which rats were reinforced for lever pressing or chain pulling in the presence of a discriminative stimulus (S), but not in its absence. In Experiment 1, extinction of the response (R) in the presence of S weakened responding in S, but equivalent nonreinforced exposure to S (without the opportunity to make R) did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 34 publications
7
53
1
Order By: Relevance
“…Instead, the rats needed an opportunity to make the response for it to be weakened during extinction. A second experiment (Bouton et al, 2016, Experiment 2) replicated the result and also demonstrated that extinction of one response (e.g., chain pulling) had no discernible impact on a second response (e.g., lever pressing) that had also been reinforced in the same stimulus. Thus, nonreinforcement of the response was necessary to produce extinction, and it suppressed only that specific response.…”
Section: Contextual Control Of Operant Extinction: a Possible Role Fomentioning
confidence: 62%
See 4 more Smart Citations
“…Instead, the rats needed an opportunity to make the response for it to be weakened during extinction. A second experiment (Bouton et al, 2016, Experiment 2) replicated the result and also demonstrated that extinction of one response (e.g., chain pulling) had no discernible impact on a second response (e.g., lever pressing) that had also been reinforced in the same stimulus. Thus, nonreinforcement of the response was necessary to produce extinction, and it suppressed only that specific response.…”
Section: Contextual Control Of Operant Extinction: a Possible Role Fomentioning
confidence: 62%
“…A series of recent experiments has produced more direct evidence suggesting response inhibition in instrumental extinction (Bouton, Trask, & Carranza-Jasso, 2016). An initial experiment showed that making the response in extinction was necessary for effective operant extinction to occur (Bouton et al, 2016, Experiment 1).…”
Section: Contextual Control Of Operant Extinction: a Possible Role Fomentioning
confidence: 99%
See 3 more Smart Citations